Kill the queen - Estep, Jennifer (Estep, Jennifer. Crown of shards., 2018)
In a realm where one<U+2019>s magical power determines one<U+2019>s worth, Lady Everleigh<U+2019>s lack of obvious ability relegates her to the shadows of the royal court of Bellona, a kingdom steeped in gladiator tradition. Seventeenth in line for the throne, Evie is nothing more than a ceremonial fixture, overlooked and mostly forgotten. But dark forces are at work inside the palace. When her cousin Vasilia, the crown princess, assassinates her mother the queen and takes the throne by force, Evie is also attacked, along with the rest of the royal family. Luckily for Evie, her secret immunity to magic helps her escape the massacre. Forced into hiding to survive, she falls in with a gladiator troupe. Though they use their talents to entertain and amuse the masses, the gladiators are actually highly trained warriors skilled in the art of war, especially Lucas Sullivan, a powerful magier with secrets of his own. Uncertain of her future<U+2014>or if she even has one<U+2014>Evie begins training with the troupe until she can decide her next move. But as the bloodthirsty Vasilia exerts her power, pushing Bellona to the brink of war, Evie<U+2019>s fate becomes clear: she must become a fearsome gladiator herself . . . and kill the queen.